STRATEGI KOMUNIKASI PERUSAHAAN DALAM MEMPROMOSIKAN LAYANAN JASA ANTAR DI PT.CITRA VAN TITIPAN KILAT (TIKI) JAKARTA - Nurul Hikmah; feri Sanjaya (FISIP Universitas Bung Karno, 2022)
The background of the study is Tiki communication strategy in promoting services between goods that can be attract consumers to use the services of the company. This study aims to determine and analyze the communication strategy of Tiki Jakarta. Facebook instalation this type of research is qualitative descriptive research with interview method, observation and documentation of TIKI research results can know the customer well, convey the message that is prepared that service Excellent, Discount, Invoicing, entertaint, and Free Pickup, set the method of promotion repeatedly, last choose 3 mainstream social media Instagram, Youtube, and Facebook. Constraints contained in customer complaints such as less educative new customers, as well as the transfer of services from offline to online, Tiki's efforts to overcome obstacles by making various forms of significant changes. Conclusion that in the activities of Corporate Communication Strategy tiki quite responsive in dealing with problems customer-facing, and able to adapt well in the digital age. Suggestions that can provide a reference for managers expedition on appropriate communication strategies in responding to consumers and can more broadly reach consumers whereverthey are